Physical and technical demands and preparatory strategies in female field collision sports: A scoping review - Dane, K.; Simms, C.; Hendricks, S.; West, S. W.; Griffin, S.; Nugent, F. J.; Farrell, G.; Mockler, D.; Wilson, F. (International Journal of Sports Medicine, 2022)
Women`s participation in field collision sports is growing worldwide. Scoping reviews provide an overview of scientific literature in a developing area to support practitioners, policy, and research priorities. Our aim is to explore published research and synthesise information on the physical and technical demands and preparation strategies of female field collision sports. We searched four databases and identified relevant published studies. Data were extracted to form (1) a numerical analysis and (2) thematic summary. Of 2318 records identified, 43 studies met the inclusion criteria. Physical demands were the most highly investigated (n+=+24), followed by technical demands (n+= 18), tactical considerations (n+=+8) and preparatory strategies (n=1). The key themes embody a holistic model contributing to both performance and injury prevention outcomes in the context of female field collision sports. Findings suggest a gender data gap across all themes and a low evidence base to inform those preparing female athletes for match demands. Given the physical and technical differences in match-demands the review findings do not support the generalisation of male-derived training data to female athletes. To support key stakeholders working within female field collision sports there is a need to increase the visibility of female athletes in the literature.